Uji Daya Hambat Ekstrak Bawang Dayak (Eleutherine palmifolia (L.) Merr.) Terhadap Pertumbuhan Bakteri Salmonella typhi - Foekh, Neiny; Utami, Ayu Putri; Aisy, Dzia Ulhaq Rohadatul (Anakes : Jurnal Ilmiah Analis Kesehatan, 2025)
Dayak onion (Eleutherine palmifolia (L.) Merr) contains many active compounds that have the potential as antibacterial, including against Salmonella typhi bacteria. This study aimed to determine the effectiveness of dayak onion powder (Eleutherine palmifolia (L.) Merr) and to determine the minimum inhibitory concentration of dayak onion extract (Eleutherine palmifolia (L.) Merr) in inhibiting the growth of Salmonella typhi bacteria. Antibacterial testing was carried out using disc diffusion, by looking at the clear area (inhibition zone) around the disc.. The design of this study was descriptive research and the results of the analysis were carried out using the Kruskal Wallis statistical test. The results showed that the extract of dayak onion (Eleutherine palmifolia (L.) Merr) at concentrations of 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90% and 100% had the ability to inhibit growth of Salmonella typhi bacteria. The average area of ​​inhibition of dayak onion extract (Eleutherine palmifolia (L.) Merr) was 7 mm, respectively; 7.3 mm; 7.6mm; 8mm; 8.3 mm; 8.6 mm; 9mm; 9.3 mm; 9.6 mm; 10.3mm. The greatest concentration of inhibition was 100% concentration with a diameter of 10.3 mm. In the blank disc negative control there was no inhibition of the growth of Salmonella typhi bacteria and in the positive control amoxicillin 500 mg there was an inhibition of 24 mm. Dayak onion extract (Eleutherine palmifolia (L.) Merr) can inhibit the growth of Salmonella typhi bacteria in the resistant category (weak) with the minimum inhibitory concentration of dayak onion extract (Eleutherine palmifolia (L.) Merr) against the growth of Salmonella typhi bacteria is 10% with an inhibition zone diameter of 7 mm.  Keywords: Dayak onion (Eleutherine palmifolia (L.) Merr), Salmonella typhi, Inhibitory test